2021
DOI: 10.31108/2.2021.4.24.6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Ukrainian expeditioners’ psychological states during long Antarctic stay

Abstract: Introduction. Extreme conditions of Antarctica and socio-spatial isolation of a small group of expeditioners’ significantly affect their physiological and psychological state. Aim. To empirically investigate the changes in the expeditioners’ psychological state indicators during a year-long Antarctic expedition. Methods. For statistical analysis were used Descriptive statistics (mean, standard deviation); One-Sample Kolmogorov-Smirnov Test; and Paired Sample T-Test. Results. The self-assessed indicators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thirdly, and most importantly, no author to date has discussed the possibility of salutogenic effects in all or even most of the expeditioners. For example, Kokun & Bakhmutova (2020, p. 11, emphasis added) noted that only ’ some expeditioners maintained a good level of psychological adaptation throughout all term of the expedition, becoming emotional and professional leaders of the station personnel'. Of course, the sample in this study included some expeditioners whose personality measures showed positive dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, and most importantly, no author to date has discussed the possibility of salutogenic effects in all or even most of the expeditioners. For example, Kokun & Bakhmutova (2020, p. 11, emphasis added) noted that only ’ some expeditioners maintained a good level of psychological adaptation throughout all term of the expedition, becoming emotional and professional leaders of the station personnel'. Of course, the sample in this study included some expeditioners whose personality measures showed positive dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers (e.g. Gunderson 1974, Palinkas & Suedfeld 2008, Leon et al 2011, Mehta & Chugh 2011, Zimmer et al 2013, Blight & Norris 2018, Suedfeld 2018, Kokun & Bakhmutova 2020) have discussed some of the negative effects on the psychological states or interpersonal relationships of expedition personnel during long periods at Antarctic bases, as well as possible positive, salutogenic effects such as successful adaptation, personal growth, spiritual and existential changes, high levels of enthusiasm, a need for achievement and optimistic future orientations.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to these negative psychological manifestations in expeditioners due to long stay at Antarctic stations, many researchers discussed possible positive psychological effects. In particular, Leon et al (2011), Mehta andChugh (2011), Zimmer et al (2013), Blight and Norris (2018), Suedfeld (2018), and Kokun and Bakhmutova (2020) pointed on possible salutogenic changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, as several researchers emphasize (Norris et al 2010;Mehta and Chugh 2011;Zimmer et al 2013;Blight and Norris 2018), some negative effects appears at psychological status or interpersonal relationships of people working for a long periods at Antarctic stations, but, at the same time, positive, salutogenic results exist also, thanks to successful adaptation to environmental adversities, accompanied by personal growth, feeling of spiritual and existential changes, high enthusiasm, optimistic future orientation and determination, need for achievement. Many expeditioners had good psychological adaptation during all expedition and became emotional and professional leaders for the station personnel (Kokun and Bakhmutova 2020).…”
Section: Introductionmentioning
confidence: 99%